Employee readiness for organizational change : Case study in a local plastic packaging manufacturing company in Java, Indonesia - Nixon, Alberth Simamora (2015)
The current high competition, globalization and free trade agreement among nations affect every business establishments today. Organizations are faced with these challenges, but to maintain their competitivenes organizations are forced to continually make necessary adjustments or change their current business strategies, operations, policies, organizational structure, and culture. However, managing these changes is as well challenging because the change process involves human mind set and behavior. To be successful, managers and other change agents desire to understand how to encourage and effectively prepare employees for change situation.The purpose of this study was to examine the determinant of employee readiness for organizational change in a local manufacturing company in Indonesia. The main research objectives were to examine the condition of employee readiness for change in this local manufacturing company, to identify significant factors affecting their readiness for change and to test whether remuneration., employee relationship with management, employee trust in management, employee receptivity to change and employee commitment to organization factors could predict employee readiness for organizational change in this local manufacturing where changes have been introduced. This empirical study proceeded by a systematic review of literature that led to development of a conceptual model.The data was collected from a sample of employees by using a survey questionnaire. Data was analyzed using descriptive statistics, exploratory factor analysis, and multiple regression analysis run on statistical package for social sciences. Results showed that independent variables (employee relationship With management, employee trust in management, employee receptivity to change and employee commitment to organization) were positively and significantly correlated to the dependent variable (employee readiness for organizational change). However, one variable (remuneration) was not found positive and significant to employee readiness for organizational change. This study provides empirical evidence for employee readiness predictor variables for organizational change. It is hoped that this study will contribute to the current literature on change managment, especially for Indonesia,and may help the management, change agents and practitioners of human resources management and development, and organizational behavior in assessing, designing and evaluating new or existing programs for organizational change.